Generation of Regulatory T Cells to Antigen Expressed in the Retina - W. McPherson, Scott; D. Heuss, Neal; Lehmann, Ute; S. Gregerson, Dale (Current Immunology Reviews (Discontinued), 2011)
Regulatory T cells (Tregs) are generated to antigens (Ag) found in the retina. Some Tregs are the result of ectopic expression of the retinal Ags in the thymus, where developing T cells are committed to enter the regulatory lineage. However, the generation of retinal Ag-specific Tregs independent of the thymus was uncertain. Our studies show that Tregs can be generated from mature, peripheral T cells based on exposure to retinal Ags. These peripherally induced Tregs limited immune responses and experimental autoimmune disease induced by retinal Ags and thus constitute a crucial component of retinal immune privilege.
Keywords: immunoregulation